2010
DOI: 10.1080/02626667.2010.487976
|View full text |Cite
|
Sign up to set email alerts
|

Simulated precipitation fields with variance-consistent interpolation

Abstract: Gridded meteorological data are available for all of Norway as time series dating from 1961. A new way of interpolating precipitation in space from observed values is proposed. Based on the criteria that interpolated precipitation fields in space should be consistent with observed spatial statistics, such as spatial mean, variance and intermittency, spatial fields of precipitation are simulated from a gamma distribution with parameters determined from observed data, adjusted for intermittency. The simulated da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…A wide selection of statistical techniques for spatial prediction exist [Lam, 1983;Li and Heap, 2011], ranging from regression to complex machine learning and simulations, and have been applied in various environmental studies [Zimmerman et al, 1999;Antonić et al, 2001;Jeffrey et al, 2001;Chen et al, 2002;Skaugen and Andersen, 2010]. Kriging interpolation is an extensively used spatial prediction method [Matheron, 1963;Goovaerts, 1997] that combines regression and weighted averaging.…”
Section: Introductionmentioning
confidence: 99%
“…A wide selection of statistical techniques for spatial prediction exist [Lam, 1983;Li and Heap, 2011], ranging from regression to complex machine learning and simulations, and have been applied in various environmental studies [Zimmerman et al, 1999;Antonić et al, 2001;Jeffrey et al, 2001;Chen et al, 2002;Skaugen and Andersen, 2010]. Kriging interpolation is an extensively used spatial prediction method [Matheron, 1963;Goovaerts, 1997] that combines regression and weighted averaging.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these comparisons have focused on temporal interpolation (Amritkar and Kumar 1995;Baltazar and Claridge 2002;Claridge and Chen 2006) or spatial interpolation in two dimensions (Holdaway 1996;Eischeid et al 2000;Skaugen and Andersen 2010). These studies applied a multitude of different interpolation methods, and found that each one performed differently depending on the data set being considered.…”
mentioning
confidence: 99%
“…The values for ν 0 and α 0 can be estimated from the observed spatial mean and standard deviation sampled from precipitation events. From analysis of 19year long time series of precipitation from various areas in Norway, the spatial mean, m , and standard deviation, s , of precipitation were found to follow a functional relationship of the type s = am (Skaugen and Andersen, 2010), where a and h are determined using nonlinear regression. Once a suitable choice of the mean of the unit is chosen, the corresponding spatial standard deviation, s , can be estimated from s = am h and ν 0 and α 0 can be determined using Eqn (2) below.…”
Section: Methodsmentioning
confidence: 99%